Bead Gel sebagai Controlled Release Urea : Pengaruh Konsentrasi Crosslinker Glutaraldehid - Lestary, Rara Ayu; Jazlina, Laili Nurin; Distantina, Sperisa (CHEMICA: Jurnal Teknik Kimia, 2018)
The structure of carboxymethylcellulose (CMC)-carrageenan mixture was chemically modified using glutaraldehyde in order to prepare bead hydrogel form. The obtained beads gel were applied to control the urea release rate. The aim of this research was to compose mathematical model describing the mass transfer rate of urea release and determine the effect of concentration glutaraldehid on the bead gel endurance in water as medium release. The bead gels (CMC/carrageenan mass ratio =1 and 2) Â were physic crosslinked with CaCl2 solution and then followed by chemically crosslinked with glutaraldehyde solution (4% & 1%) using immersion method and thermal curing at 110oC for 25 minutes. After being washed and dried, the beads gel were immersed in urea solution. The rate release of urea from dried crosslinked beads gel in water was determined by measuring the concentration of urea in various time of immersion. The result showed that the mathematical model arranged could describe the mass transfer rate of urea release. The higher glutaraldehid concentration on beads gel, the higher beads gel endurance in water.